Evaluasi Implementasi Prepopulated Error System Pada Aplikasi Efaktur 3.0 - Raden Kusyeni; Ryan Nugraha (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The modernization program gave by the Directorate General of Taxes (DGT) in further developing the assistance nature of PKP citizens in the tax assessment area through guiding the pre-populated 3.0 e-faktur application is thought of as viable and adequate to citizens. The consequences of past investigations discovered that steering this application can lessen contributing mistakes on input charge solicitations physically, make it simpler to report VAT period expense forms, to work on the nature of administrations did by the Directorate General of Taxes. Be that as it may, with the expanding nature of administration for citizens, steering this application additionally needs to assess the issues and requirements experienced by citizens in showing and working this application to taking a stock of pre-populated VAT Tax Returns (SPT) issues and approving Import Notifications of Goods ( PIB). Does this application framework actually must be updated in running and working it (Error System), and what are the answers for manage issues and hindrances in case of a framework mistake that is frequently capable by citizens in working this application. The motivation behind this study is to make it simpler for citizens to deal with issues and impediments in the blunder framework application, assess the execution of pre-populated VAT returns subsequent to running the pre-populated e-receipt 3.0 application. This examination strategy utilizes subjective techniques with information assortment cycles and specialized information investigation. Information examination information sources are acquired from information assortment through e-research, subjective methodologies through meetings and perceptions. The aftereffects of the discoveries of this study are relied upon to give direction on the straightforwardness and perfection of the Directorate General of Taxes (DGT) in expanding the utilization of this pre-populated e-receipt 3.0. It is likewise an extra knowledge into data for scientists, instructors/speakers and citizens. Turn into a reference and extra data for the Directorate General of Taxes in working on the nature of assessment administrations, as well just like a wellspring of guidance and contribution for strategy producers. Subsequently, the creator raises research on e-invoicing applications that frequently experience framework blunders in their activities.